Educomunicação, língua-cultura guarani, sustentabilidade Teko Porã: myasãimbo’e, avañe’ẽ ayvu-arandu, ñeñangareko ha bom viver - Villalva Filho, Mario Ramão (2020)
This research has aimed mainly at fulfilling demands for qualification of the indigenous communities of Añetete and Itamarã, in the city of Diamante do OestePR. In order to understand those demands in more detail, a survey was carried out in 2017 based on field research conducted within the " Extensão Inovadora e Desenvolvimento Rural Sustentável" course in the PPGDRS (Graduate Program in Sustainable Rural Development) at UNIOESTE. Based on this experience, in 2018 a outreach project was designed at the Federal University of Latin American Integration (UNILA), focusing on Educommunication methodological approaches. The outreach project in indigenous schools in the communities of Añetete and Itamarã has aimed to provide Guarani teachers with class preparation guides and resources. In 2019, the outreach project was strengthened and expanded, with the participation of volunteers and collaborators. In this way, several workshops were held for children at the Araju Porã school (Itamarã) and for young leaders in the Opy (Praying House) of both villages. Based on the dialogical methodology employed by Educommunication, these activities were not intended to solely provide capacity building, but also to receive capacity building, in a two-way basis, sharing knowledge with our project team, as well as exchanging social, cultural and educational practices, so as to present them to society at large through the productions resulting from the activities carried out in the villages. In this sense, such a process would not have been possible without an understanding of Guarani philosophy, as well as its history and its influence in several countries. Such philosophy can be summarized in two words, Teko Porã, which implies the ―Good Way of Being‖. Thus, the meanings of sustainability were analyzed from that Guarani philosophical perspective through its current wise elders, as well as through the written literature, from Anchieta, Montoya and Restivo, to Cadogan, Meliá, Viveiros de Castro and other contemporary authors who have been put into dialogue in this research. Therefore, the voices of indigenous writers and academics have been sought in this study because they conceive the Guarani wisdom that will guide us to a more sustainable and possible world.